Validation of an algorithm based on clinical, histopathological and immunohistochemical data for the diagnosis of early-stage mycosis fungoides, - Gustavo Moreira Amorim; Daniele Carvalho Quintella; João Paulo Niemeyer-Corbellini; Luiz Claudio Ferreira; Marcia Ramos-; Tullia Cuzzi (Sociedade Brasileira de Dermatologia, 2020)
Abstract Background: Diagnosis of mycosis fungoides is challenging due to the non-specificity of clinical and histopathological findings. The literature indicates an average delay of 4-6 years for a conclusive diagnosis. Refinement of the histopathological criteria for the diagnosis of patients in early stages of the disease is considered of interest. Objectives: To study the histopathological aspects of early-stage mycosis fungoides and the applicability, in a retrospective form, of the diagnostic algorithm proposed by Pimpinelli et al. Methods: Observational, retrospective, transversal study based on revision of histopathological exams of patients with suspected mycosis fungoides. Medical records were reviewed, and complementary immunohistochemistry performed. Results: Sixty-seven patients were included. The most frequent histopathological features were superficial perivascular lymphoid infiltrate (71.6%), epidermotropism (68.7%), lymphocytic atypia (63.8%), hyperkeratosis (62.7%) and acanthosis (62.7%). Forty-three patients scored 4 points at the algorithm, by clinical and histological evaluation. Immunohistochemistry was performed on 23 of the 24 patients with less than 4 points. Of those 23, 22 scored 1 point, allowing a total of 61 patients (91%) with the diagnosis of early-stage mycosis fungoides. Study limitations: Its retrospective character, reduced sample size and incomplete application of the algorithm. Conclusions: Application of the Pimpinelli et al. algorithm, even in an incomplete form, increased the percentage of cases diagnosed as mycosis fungoides. Routine application of the algorithm may contribute to earlier and specific management and improvement of the patients' outcome.